2020
DOI: 10.7759/cureus.11279
|View full text |Cite
|
Sign up to set email alerts
|

A Needle in the Haystack: A Rare Case of Spontaneous Tumor Lysis in Newly Diagnosed Chronic Lymphocytic Leukemia Unmasked by Acute Renal Failure

Abstract: Tumor lysis syndrome (TLS) is the phenomenon of metabolic derangements that typically follows the initiation of cytotoxic chemotherapy. Metabolic disturbances include hyperphosphatemia, hyperkalemia, hyperuricemia and hypocalcemia. Hematological malignancies are associated with spontaneous TLS (STLS), which is cell lysis in the absence of chemotherapy. STLS is extremely rare in chronic lymphocytic leukemia (CLL). This has been documented only once in the medical literature, making this an extraordinarily uncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Symptoms manifest as life-threatening organ dysfunction, such as acute renal failure and cardiac arrhythmia [ 8 ]. While an exact incidence is not known, spontaneous TLS is understood to rarely occur, although cases have been reported [ 9 , 10 ]. One study showed that three out of 33 patients with non-Hodgkin’s lymphoma (NHL) had marked hyperuricemia and acute kidney injury before receiving chemotherapy [ 11 ], which was also seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms manifest as life-threatening organ dysfunction, such as acute renal failure and cardiac arrhythmia [ 8 ]. While an exact incidence is not known, spontaneous TLS is understood to rarely occur, although cases have been reported [ 9 , 10 ]. One study showed that three out of 33 patients with non-Hodgkin’s lymphoma (NHL) had marked hyperuricemia and acute kidney injury before receiving chemotherapy [ 11 ], which was also seen in our patient.…”
Section: Discussionmentioning
confidence: 99%